Managing Project Scope Shortcuts to success - Harrin, Elizabeth (BCS, The Chartered Institute for IT, 2013)
Project scope forms part of the 'golden triangle' of project management along with resources and time. If there is a change to any part of the triangle, another element has to change to keep the balance. This ebook helps project managers to understand how their project fits into the overall strategy of an organisation, how to avoid the traps of assumptions, manage risks and prevent scope creep. This is one section of the book "Shortcuts to Success".